FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS INFORMASI LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi pada OPD Kabupaten Deli Serdang) - Kesuma Puja Lestari; Afrah Junita; Iqlima Azhar (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2023)
This study aims to determine the effect of human resource competence, government accounting standards and government internal control systems on the quality of local government financial reporting information. The sampling technique in this study was purposive sampling, namely sampling with certain considerations with a total sample of 93 respondents. Methods of data collection using a questionnaire. The data analysis method used is multiple linear regression. The results of this study indicate that the competence of human resources has an effect positive and significant to the quality of local government financial report information. Government accounting standards have a positive and significant effect on quality of local government financial reporting information. The government's internal control system has a positive and significant effect on the quality of report information local government finances. Competence of human resources, government accounting standards and the government's internal control system simultaneously affect the quality of local government financial report information in Deli Serdang Regency.